A preliminary survey on the awareness of the existence of megalithic culture and the need for the digitisation - Sri Yanti Mahadzir; Zurina Muda; Siti Aishah Hanawi (Penerbit Universiti Kebangsaan Malaysia, 2025)
Megaliths are remnants of the cultural heritage of the local community in Malaysia that are no longer practiced in the lives of today’s society. Nonetheless, They are important monuments in archaeological and historical studies, providing important insights into the life and beliefs of ancient societies. The use of traditional data storage methods, limitations in information sharing and delivery, and lack of public awareness of existing megaliths have caused have caused these structures to be increasingly lost and forgotten in today’s world. Therefore, this study aims to identify the level of respondents’ awareness of megaliths in Malaysia and user requirements to digitise information on megalithic culture, especially in Negeri Sembilan. This study conducted a preliminary survey, with a questionnaire serving as the data collection instrument. This survey included 70 respondents from the Faculty of Social Sciences and Humanities and the ICT Center at Universiti Kebangsaan Malaysia (UKM), selected using the purposive sampling approach. The data obtained were analyzed using IBM SPSS Statistics version 28. The findings of the study showed that 56% of respondents knew about the presence of megalithic stones in Malaysia and it indicating a moderate level of knowledge and awareness. In addition, this survey highlights the high need and demand for digital information with 100% of respondents agreeing that the dissemination of information today is more effective through a digital approach. These findings will guide the next phase of this study, specifically, the development phase of digital technology application. Hopefully, the effort will raise awareness among the new generation on the importance of preserving the megalithic cultural heritage.